2011
DOI: 10.1371/journal.pone.0016704
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Brain β-Endorphin Concentration by the Specific Part of the Y Chromosome in Mice

Abstract: BackgroundSeveral studies in animal models suggest a possible effect of the specific part of the Y-chromosome (YNPAR) on brain opioid, and more specifically on brain β-endorphin (BE). In humans, male prevalence is found in autistic disorder in which observation of abnormal peripheral or central BE levels are also reported. This suggests gender differences in BE associated with genetic factors and more precisely with YNPAR.Methodology/Principal FindingsBrain BE levels and plasma testosterone concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, we showed in this study that fetal alcohol-induced hypermethylation of Pomc gene in sperm transferred accross three generations. Recently it has been shown that the non-paring part of the Y-chromosome influences the expression of BEP in the hypothalamus (44). Additionally, the transcription of Mc2R a POMC receptor, is dependent on the Sry gene (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed in this study that fetal alcohol-induced hypermethylation of Pomc gene in sperm transferred accross three generations. Recently it has been shown that the non-paring part of the Y-chromosome influences the expression of BEP in the hypothalamus (44). Additionally, the transcription of Mc2R a POMC receptor, is dependent on the Sry gene (45).…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothalamus, POMC is regulated in part by the non‐pairing region of the Y chromosome (Y NPAR ) (Botbol et al . ). Additionally, transgenerational changes in the expression of the Pomc gene in rats were detected in sperm (Botbol et al .…”
Section: Hypothetical Mechanism Of Transgenerational Transmission Of mentioning
confidence: 97%
“…The reason why methylation patterns on this gene along the male germline can be preserved and escape reprogramming during development is unknown. A possible explanation for this would be, since the phenotype is only passed down along the male germline and Pomc expression is regulated by the non-pairing region of the Y chromosome (Botbol et al, 2011), alcohol exposure leads to epigenetic modifications on the Y chromosome that are spared from reprogramming during development and are then passed down to subsequent generations (Sarkar, 2016). Future studies are needed to address this possibility.…”
Section: Possible Mechanisms For Germline-dependent Epigenetic Inhmentioning
confidence: 99%